Cecal duplication cyst complicated by prolapsed ileocolic intussusception - Afshar Ghamari khameneh, MD; Gisoo Darban Hosseini Amirkhiz, MD; Seyed Ali Alamdaran, MD; Paria Dehghanian, MD (Elsevier, 2020)
Cecal duplication cysts are very rare including 0.4% of all GI tract duplications. The ultrasound (US) is the imaging of choice for duplication cysts detection in pediatrics. Cyst's wall is made up of an inner mucosal layer, which is echogenic and an outer muscular layer, which is hypoechoic at US (called "pseudo kidney" appearance on longitudinal view or "doughnut" appearance on transverse view). Intussusception is one of the duplication cyst's complications. Intussusception presented with trans-anal protrusion (prolapsed intussusception) is a rare and confusing condition which can cause delayed diagnosis and further complications.We present an 18-month old boy with Cecal duplication cyst causing intussusception, which protruded from anus. Keywords: Cecal duplication cyst, Ileocolic intussusception, Prolapsed intussusception